A modified phenolic resin for formaldehyde zero-increment plywood and its preparation method and application

By optimizing the formulation and process of phenolic resin, a modified phenolic resin for plywood was prepared, which solved the problem of insufficient formaldehyde emission and environmental protection performance in existing plywood, and achieved ultra-low formaldehyde emission and excellent glue performance.

CN119735774APending Publication Date: 2025-04-01DYNEA GUANGDONG +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411961664.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The aldehyde adhesives used in the production of existing plywood have problems such as formaldehyde emission and insufficient environmental protection performance, and the aldehyde-free adhesives have shortcomings in terms of glue performance and storage stability.

Method used

By using phenol, formaldehyde, catalyst, urea and lignin as the main raw materials, after formula and process optimization, a modified phenolic resin for zero-increment plywood was prepared, and applied in plywood to achieve ultra-low formaldehyde emission.

Benefits of technology

The prepared plywood has an ultra-low formaldehyde emission, close to the formaldehyde emission of log veneer, and has good glue strength, water resistance and storage stability, and has excellent environmental protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735774A_ABST
    Figure CN119735774A_ABST
Patent Text Reader

Abstract

The invention discloses a modified phenolic resin for formaldehyde zero-increment plywood, a preparation method and an application thereof, and belongs to the technical field of wood processing. The raw materials of the modified phenolic resin for formaldehyde zero-increment plywood of the invention include, by mass, 100 parts of phenol, 118-286 parts of formaldehyde solution, 8-20 parts of urea, 25-60 parts of lignin, 25-55 parts of catalyst and 112-436 parts of water. In the synthesis process of the modified phenolic resin of the invention, by introducing urea and lignin as modifiers, and by accurately controlling the material amount and process of each step, the prepared plywood can have an ultra-low formaldehyde emission, so that the formaldehyde emission of the plywood is not significantly different from the formaldehyde emission of the wood veneer itself.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wood processing, in particular to a modified phenolic resin for formaldehyde zero-increment plywood and a preparation method and application thereof. Background Art

[0002] Plywood is a three-layer or more board made by peeling a certain length of wood into a certain size of veneer, applying adhesive on its surface, arranging adjacent layers of veneer fiber texture perpendicular to each other, and pressing under certain conditions. Plywood is a wood composite material reorganized with peeled veneer as the basic unit. It has the advantages of good solid wood feel, excellent physical and mechanical properties and good processing performance. It is accepted by consumers and has become the mainstream variety of artificial boards.

[0003] Most of the existing plywood production uses aldehyde adhesives such as urea-formaldehyde resin, phenol-formaldehyde resin or melamine-modified resin. These adhesives are used to produce plywood and have the characteristics of high bonding strength, fast curing, low cost and abundant raw material sources. However, free formaldehyde, TVOC, dust and other harmful substances will be released during the production and use process, causing adverse effects. In recent years, due to the defects of aldehyde adhesives in environmental performance and other aspects, formaldehyde-free adhesives have received more and more attention from academia and industry. Soy protein and its modified resin have the advantages of environmental protection, wide source of raw materials and degradability, but there are problems such as poor bonding performance, low storage stability, poor water resistance and easy mildew, which limit the large-scale promotion and application of this type of adhesive. Water-based isocyanate resin is used in the production of plywood, which has the advantages of good water resistance, high bonding strength and no formaldehyde release, but the production cost is high, the raw material toxicity is high, and the initial adhesion is poor. There is also room for further improvement. Summary of the invention

[0004] The object of the present invention is to provide a modified phenolic resin for formaldehyde zero-increment plywood and a preparation method and application thereof, so as to solve the problems in the background technology. In the present invention, phenol, formaldehyde, catalyst, urea and lignin are used as main raw materials, and after optimizing the formula and process such as raw material ratio, feeding sequence, reaction temperature, polycondensation end point, a phenolic resin for formaldehyde zero-increment plywood is prepared, and it is applied to plywood to produce a plywood with a formaldehyde release amount that is not significantly different from that of a wood veneer. In the synthesis process of the modified phenolic resin of the present invention, by introducing urea and lignin as modifiers, and by accurately controlling the material amount and process of each step, the prepared plywood can have an ultra-low formaldehyde release amount, so that the formaldehyde release amount of the plywood is not significantly different from that of the original wood veneer itself.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a modified phenolic resin for formaldehyde zero-increment plywood, wherein the raw materials, calculated by weight, include:

[0007] 100 parts of phenol, 118-286 parts of formaldehyde solution, 8-20 parts of urea, 25-60 parts of lignin, 25-55 parts of catalyst and 112-436 parts of water.

[0008] Preferably, the catalyst is sodium hydroxide and / or potassium hydroxide.

[0009] Preferably, the formaldehyde solution is a formaldehyde aqueous solution with a concentration of 35-55 wt%.

[0010] Preferably, the molar ratio of formaldehyde to phenol in the formaldehyde solution is (2.0-3.0):1.

[0011] The second technical solution of the present invention is to provide a method for preparing the modified phenolic resin for the above-mentioned formaldehyde zero-increment plywood, comprising the following steps:

[0012] Feeding the formaldehyde solution, urea, catalyst and water in two batches;

[0013] Phenol, the first batch of water, the first batch of formaldehyde solution and the first batch of catalyst are mixed to carry out the first heating reaction; then the second batch of formaldehyde solution is added to carry out the second heating reaction; then lignin and the first batch of urea are added to carry out the third heating reaction; then the second batch of water, the second batch of catalyst and the second batch of urea are added, the temperature is lowered and the material is discharged to obtain the modified phenolic resin for the formaldehyde zero-increment plywood.

[0014] Preferably, the mass ratio of the first batch of formaldehyde solution to the second batch of formaldehyde solution is (0.8-2.0):1; the mass ratio of the first batch of urea to the second batch of urea is 1:(1-1.5); the mass ratio of the first batch of catalyst to the second batch of catalyst is (1.5-2):1; the mass ratio of the first batch of water to the second batch of water is 1:(1.5-5.0).

[0015] Preferably, the temperature of the first heating reaction is 60-70°C, and the time is 1-2h; the temperature of the second heating reaction is 70-90°C, and the time is 2-4h; the temperature of the third heating reaction is 70-80°C, and the time is 2-3h.

[0016] The modified phenolic resin prepared by the method of the invention has a viscosity of 30-150 mPa·s, a solid content of 30-50%, a pH value of 10-12, free formaldehyde ≤0.2%, and free phenol ≤0.2%.

[0017] The third technical solution of the present invention is to provide an application of the modified phenolic resin in the preparation of formaldehyde zero-increment plywood.

[0018] The fourth technical solution of the present invention is to provide a formaldehyde zero-increment plywood, using the above-mentioned modified phenolic resin as a bonding component between the board layers.

[0019] The fifth technical solution of the present invention is to provide a method for preparing the above-mentioned formaldehyde zero-increment plywood, comprising the following steps:

[0020] (1) Peeling and drying of veneers: Peeling wood into veneers and drying them to obtain wood veneers;

[0021] (2) preparing adhesive: uniformly mixing the modified phenolic resin, flour and mineral filler with a mixer to obtain a mixed adhesive;

[0022] (3) Gluing and assembling: placing the mixed adhesive into a glue coating machine, using a glue coating roller to evenly coat the mixed adhesive on the surface of the wood veneer, and then assembling the veneers in the longitudinal and transverse directions to obtain plywood slabs;

[0023] (4) Pre-pressing and aging: placing the plywood blank into a cold press for pre-pressing and aging to obtain a pre-pressed blank;

[0024] (5) Hot pressing: sending the pre-pressed slab into a hot press for hot pressing to obtain the formaldehyde zero-increment plywood.

[0025] Furthermore, the method for preparing the formaldehyde zero-increment plywood comprises the following steps:

[0026] (1) Peeling and drying of veneers: Peel the wood into log veneers with a thickness of 1.5-3.5 mm, place them in a drying device, and dry them to a moisture content of 8-12% to obtain wood veneers;

[0027] (2) Glue preparation: uniformly mixing the modified phenolic resin, flour and mineral filler to obtain a bonding component;

[0028] (3) Gluing: Applying adhesive components on the surfaces to be joined between adjacent single-layer boards;

[0029] (4) Assembling: Assembling the single-layer boards after gluing in step (3) in a direction in which the wood grain is perpendicular to each other, wherein the number of layers of the single-layer boards is an odd number of 3 to 11, to obtain a slab;

[0030] (5) Open aging: The slab is placed at room temperature for open aging for 0.5-8.0 h;

[0031] (6) Cold pressing: the assembled blank aged in step (5) is pressed at a pressure of 0.8-2.0 MPa for 30-60 min to obtain a cold pressed blank;

[0032] (7) Closed-mouth aging: The cold-pressed slab is aged at room temperature for 0-3 h;

[0033] (8) Hot pressing: placing the cold pressed blank aged in step (7) in a hot press for hot pressing to obtain a formaldehyde zero-increment plywood; the hot pressing pressure is 0.8-2.0 MPa, the temperature is 120-130° C., and the time is 1.0-3.0 min / mm.

[0034] Furthermore, the mineral filler is one or more of kaolin, attapulgite and montmorillonite; and the mass ratio of the modified phenolic resin, flour and mineral filler is 100:(5-30):(10-20).

[0035] Furthermore, the single-layer board is made of poplar, eucalyptus, birch or fir.

[0036] Furthermore, the coating has a single-sided glue application amount of 150-200 g / cm 2 .

[0037] The beneficial technical effects of the present invention are as follows:

[0038] In the synthesis process of the modified phenolic resin of the present invention, by introducing urea and lignin as modifiers and by accurately controlling the material amount and process of each step, the prepared plywood can have an ultra-low formaldehyde emission, and the formaldehyde emission of the plywood is not significantly different from that of the original wood veneer itself.

[0039] The modified phenolic resin of the present invention also has the advantages of low price, mildew and corrosion resistance, strong process adaptability, good water resistance, high bonding strength, mildew and corrosion resistance, mild synthesis conditions, green and environmentally friendly characteristics, and also has good storage stability.

[0040] The mineral filler added in the present invention reduces the occurrence of board explosion, reduces the amount of modified phenolic resin used, and further reduces the formaldehyde emission of the plywood while ensuring the excellent bonding performance of the plywood.

[0041] The formaldehyde zero-increment plywood prepared by the present invention has excellent environmental performance, ultra-low formaldehyde emission and TVOC emission rate; formaldehyde emission ≤ 0.010 mg / m 3 (climate chamber method), lower than E NF Limit (≤0.025mg / m 3 ), according to the test method of "Technical Requirements for Environmental Labeling Products - Wood-Based Panels and Their Products" (HJ 571-2010), the TVOC release rate can be as low as ≤0.01mg·m -2 ·h -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 The present invention is a process flow chart for preparing formaldehyde zero-increment plywood.

[0044] Figure 2 This is a physical picture of the modified phenolic resin used for the formaldehyde zero-increase plywood in Example 1.

[0045] Figure 3 This is a real picture of the formaldehyde zero-increment plywood in Effect Example 1.

[0046] Figure 4 This is a real picture of the plywood in comparative example 6. DETAILED DESCRIPTION

[0047] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0048] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0049] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0050] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0051] The national standard "Classification of Formaldehyde Emission of Artificial Boards and Their Products" (GB / T 39600-2021) divides the formaldehyde emission of artificial boards and their products into three levels from low to high: E NF E0 and E1, among which E NFThe formaldehyde emission level specified in the standard is ≤0.025mg / m 3 .

[0052] The present invention provides a method for preparing formaldehyde zero-increment plywood, comprising the following steps:

[0053] The modified phenolic resin, flour and mineral filler are mixed to obtain a bonding component;

[0054] The bonding component is coated on the surface to be spliced ​​of the single-layer board, and then spliced ​​to obtain a blank; the blank is pressed to obtain the formaldehyde zero-increment plywood.

[0055] The formaldehyde solution used in the following examples and comparative examples of the present invention is a formaldehyde aqueous solution with a concentration of 35-55wt%.

[0056] Unless otherwise specified, the parts in the present invention are all calculated by mass.

[0057] The "room temperature" in the present invention is 10-30°C unless otherwise specified.

[0058] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.

[0059] Figure 1 The present invention is a process flow chart for preparing formaldehyde zero-increment plywood.

[0060] Figure 2 This is a physical picture of the modified phenolic resin used for the formaldehyde zero-increase plywood in Example 1.

[0061] In the following test data, the TVOC emission rate is tested according to the method of "Technical Requirements for Environmental Labeling Products - Artificial Boards and Their Products" (HJ571-2010), the formaldehyde emission is tested according to the method of "Test Methods for Physical and Chemical Properties of Artificial Boards and Veneered Artificial Boards" (GB / T17657-2022), and the bonding strength and immersion peeling properties are tested according to the method of "Ordinary Plywood" (GB / T 9846-2015).

[0062] Example 1

[0063] A method for preparing a modified phenolic resin comprises the following steps:

[0064] 100 parts of phenol, 79 parts of water, 102 parts of formaldehyde solution with a mass concentration of 44% and 24 parts of sodium hydroxide were added to the reactor, and the temperature was raised to 65°C and kept for 1.5 hours; 74 parts of formaldehyde solution with a mass concentration of 44% were added, and the temperature was raised to 80°C and kept for 3 hours. After the heat preservation was completed, 42.5 parts of lignin and 6 parts of urea were added, and the temperature was kept at 75°C for 2.5 hours. 8 parts of urea, 200 parts of water and 13.5 parts of sodium hydroxide were added, and the temperature was cooled to 25°C to obtain a modified phenolic resin for formaldehyde zero-increment plywood. The resin viscosity was measured to be 53mPa·s, the solid content was 35.4%, the pH value was 10.9, the free formaldehyde was 0.09%, and the free phenol was 0.13%.

[0065] Example 2

[0066] A method for preparing a modified phenolic resin comprises the following steps:

[0067] 100 parts of phenol, 40 parts of water, 87 parts of 50% formaldehyde solution and 7 parts of potassium hydroxide were added to the reactor, and the temperature was raised to 70°C for 2 hours; 43 parts of 50% formaldehyde solution were added, and the temperature was raised to 90°C for 2 hours. After the insulation, 25 parts of lignin and 4 parts of urea were added, and the temperature was kept at 80°C for 2 hours. 4 parts of urea, 60 parts of water and 13 parts of potassium hydroxide were added, and the temperature was cooled to 25°C to obtain a modified phenolic resin for formaldehyde zero-increment plywood. The resin viscosity was measured to be 145mPa·s, the solid content was 49.8%, the pH value was 10.3, the free formaldehyde was 0.06%, and the free phenol was 0.15%.

[0068] Example 3

[0069] A method for preparing a modified phenolic resin comprises the following steps:

[0070] 100 parts of phenol, 80 parts of water, 108 parts of formaldehyde solution with a mass concentration of 37% and 37 parts of sodium hydroxide were added to the reactor, and the temperature was raised to 60°C and kept for 1 hour; 135 parts of formaldehyde solution with a mass concentration of 37% were added, and the temperature was raised to 70°C and kept for 4 hours. After the insulation was completed, 60 parts of lignin and 8 parts of urea were added, and the temperature was kept at 80°C for 3 hours. 12 parts of urea, 357 parts of water and 18 parts of sodium hydroxide were added, and the temperature was cooled to 25°C to obtain a modified phenolic resin for formaldehyde zero-increment plywood. The resin viscosity was measured to be 35mPa·s, the solid content was 30.1%, the pH value was 11.8, the free formaldehyde was 0.13%, and the free phenol was 0.08%.

[0071] Comparative Example 1

[0072] The same as Example 1, except that the amount of the second batch of formaldehyde solution with a mass concentration of 44% was changed from 74 parts to 148 parts. The prepared phenolic resin had a viscosity of 50 mPa·s, a solid content of 37.2%, a pH value of 10.7, 0.34% free formaldehyde, and 0.07% free phenol.

[0073] Comparative Example 2

[0074] The same as Example 1, except that the amount of the second batch of formaldehyde solution with a mass concentration of 44% was changed from 74 parts to 23 parts. The prepared phenolic resin had a viscosity of 64 mPa·s, a solid content of 34.1%, a pH value of 11.4, 0.05% free formaldehyde, and 0.67% free phenol.

[0075] Comparative Example 3

[0076] The same as Example 1, except that no lignin and urea were added. The prepared phenolic resin had a viscosity of 38 mPa·s, a solid content of 29.8%, a pH value of 11.5, 0.58% free formaldehyde, and 0.15% free phenol.

[0077] Comparative Example 4

[0078] The same as Example 1, except that no lignin was added. The prepared phenolic resin had a viscosity of 42 mPa·s, a solid content of 31.4%, a pH value of 11.4, free formaldehyde of 0.39%, and free phenol of 0.09%.

[0079] Comparative Example 5 (one-step synthesis of resin)

[0080] A preparation method of a phenolic resin adhesive, the steps are as follows:

[0081] 100 parts of phenol, 279 parts of water, 176 parts of formaldehyde solution with a mass concentration of 44%, 37.5 parts of sodium hydroxide, 42.5 parts of lignin and 14 parts of urea were added to a reactor, heated to 65°C and kept for 1.5 hours, then heated to 80°C and kept for 3 hours, then cooled to 75°C and kept for 2.5 hours, and then cooled to 25°C to obtain a phenolic resin adhesive. The resin viscosity was measured to be 200 mPa·s, the solid content was 36.1%, the pH value was 10.9, the free formaldehyde was 0.21%, and the free phenol was 0.25%.

[0082] Effect Example 1

[0083] A method for preparing formaldehyde zero-increment plywood, comprising the following steps:

[0084] (1) Veneer peeling and drying: The eucalyptus wood is peeled into eucalyptus veneers with a thickness of 1.7 mm and placed in a drying device, and dried to a moisture content of 10% to obtain a single-layer board;

[0085] (2) Glue preparation: the modified phenolic resin, flour and kaolin in Example 1 were mixed in a ratio of 100:15:15;

[0086] (3) Gluing: 175g / cm on each side of the single-layer board to be glued. 2 The adhesive component is coated with an amount of sizing;

[0087] (4) Assembling the blanks: assembling the single-layer boards after gluing in step (3) in a direction in which the wood grains are perpendicular to each other, wherein the number of layers of the single-layer boards is 7, to obtain blanks;

[0088] (5) Open aging: The slab is placed in an open state at room temperature for 2 h;

[0089] (6) Cold pressing: the assembled blank aged in step (5) is pressed at a pressure of 1.0 MPa for 45 min to obtain a cold pressed blank;

[0090] (7) Closed-mouth aging: The cold-pressed slab is aged at room temperature for 2 h;

[0091] (8) Hot pressing: The cold pressed blank aged in step (7) is placed in a hot press for hot pressing to obtain a formaldehyde zero-increment plywood; the hot pressing pressure is 1.2 MPa, the temperature is 125° C., and the hot pressing time is 17.9 min (7×1.7 mm×1.5 min / mm=17.9 min).

[0092] Figure 3 This is a real picture of the formaldehyde zero-increment plywood in Effect Example 1.

[0093] The actual picture of the formaldehyde zero-increase eucalyptus plywood produced in this effect example is shown in Figure 3 The formaldehyde emission is measured to be 0.007 mg / m 3 (climate chamber method), TVOC release rate was not detected (detection limit was 0.01 mg·m -2 ·h -1 ), the bonding strength is 1.14MPa (Class I board condition), and the immersion peeling pass rate is 100% (Class I board condition).

[0094] Effect Example 2

[0095] A method for preparing formaldehyde zero-increment plywood, comprising the following steps:

[0096] (1) Peeling and drying of veneers: Peel the poplar wood into 1.5 mm thick poplar veneers and place them in a drying device, and dry them to a moisture content of 8% to obtain a single-layer board;

[0097] (2) Glue preparation: the modified phenolic resin, flour and attapulgite in Example 1 were mixed in a ratio of 100:10:20;

[0098] (3) Gluing: 185g / cm on each side of the single-layer board to be glued. 2 The adhesive component is coated with an amount of sizing;

[0099] (4) Assembling blanks: assembling the single-layer boards after gluing in step (3) in a direction in which the wood grains are perpendicular to each other, wherein the number of layers of the single-layer boards is 11, to obtain blanks;

[0100] (5) Open aging: The slab is placed at room temperature for open aging for 1.5 h;

[0101] (6) Cold pressing: the slab aged in step (5) is pressed at a pressure of 0.8 MPa for 50 min to obtain a cold pressed assembly;

[0102] (7) Closed-mouth aging: The cold-pressed slab is aged at room temperature for 1 h;

[0103] (8) Hot pressing: The cold pressed blank aged in step (7) is placed in a hot press for hot pressing to obtain a formaldehyde zero-increment plywood; the hot pressing pressure is 1.5 MPa, the temperature is 125° C., and the time is 18.2 min (11×1.5 mm×1.1 min / mm=18.2 min).

[0104] The formaldehyde emission of the zero-increase poplar plywood produced in this example was measured to be 0.007 mg / m 3 , TVOC release rate is 0.01mg·m -2 ·h -1 The bonding strength is 1.34MPa (Class I board conditions), and the immersion peeling pass rate is 100% (Class I board conditions).

[0105] Effect Example 3

[0106] A method for preparing formaldehyde zero-increment plywood, comprising the following steps:

[0107] (1) Peeling and drying of veneers: Peel birch wood into birch veneers with a thickness of 2.5 mm and place them in a drying device to dry them to a moisture content of 12% to obtain a single-layer board;

[0108] (2) Glue preparation: the modified phenolic resin, flour and montmorillonite in Example 2 are mixed uniformly in a mass ratio of 100:5:10 to obtain a bonding component;

[0109] (3) Gluing: 150g / cm on each side of the single-layer board to be glued. 2 The adhesive component is coated with an amount of sizing;

[0110] (4) Assembling: Assembling the single-layer boards after gluing in step (3) in a direction perpendicular to the wood grain, wherein the number of layers of the single-layer boards is 5, to obtain a slab;

[0111] (5) Open aging: The slab is placed at room temperature for open aging for 0.5 h;

[0112] (6) Cold pressing: the assembled blank after aging in step (5) is pressed at a pressure of 1.5 MPa for 30 min to obtain a cold pressed blank;

[0113] (7) Closed-mouth aging: The cold-pressed slab is aged at room temperature for 3 h;

[0114] (8) Hot pressing: The cold pressed blank aged in step (7) is placed in a hot press for hot pressing to obtain a formaldehyde zero-increment plywood; the hot pressing pressure is 0.8 MPa, the temperature is 130°C, and the time is 25 min (5×2.5 mm×2.00 min / mm=25 min).

[0115] The formaldehyde emission of the zero-increase birch plywood produced in this example was measured to be 0.008 mg / m 3 The TVOC release rate is 0.03 mg·m -2 ·h -1 The bonding strength is 0.92MPa (Class II board conditions), and the immersion peeling pass rate is 100% (Class II board conditions).

[0116] Effect Example 4

[0117] A method for preparing formaldehyde zero-increment plywood, comprising the following steps:

[0118] (1) Peeling and drying of veneers: Peel the fir wood into 3.5 mm thick fir veneers and place them in a drying device to dry them to a moisture content of 10% to obtain a single-layer board;

[0119] (2) Glue preparation: the modified phenolic resin, flour and kaolin filler in Example 3 are mixed uniformly in a mass ratio of 100:30:12 to obtain a bonding component;

[0120] (3) Gluing: 200g / cm on each side of the single-layer board to be glued. 2 The adhesive component is coated with an amount of sizing;

[0121] (4) Assembling: Assembling the single-layer boards after gluing in step (3) in a direction perpendicular to the wood grain, wherein the number of layers of the single-layer boards is three, to obtain a slab;

[0122] (5) Open aging: The slab is placed in an open state for 3 h at room temperature;

[0123] (6) Cold pressing: The slab aged in step (5) is pressed at a pressure of 2 MPa for 60 min to obtain a cold pressed slab;

[0124] (7) Closed-mouth aging: The cold-pressed slab is aged at room temperature for 0 h;

[0125] (8) Hot pressing: The cold pressed blanks aged in step (7) are placed in a hot press for hot pressing to obtain a formaldehyde zero-increment plywood; the hot pressing pressure is 2 MPa, the temperature is 120°C, and the time is 29.4 min. (3×3.5 mm×2.8 min / mm=29.4 min)

[0126] The formaldehyde emission of the zero-increase fir plywood produced in this example was measured to be 0.006 mg / m 3 The TVOC release rate is 0.02 mg·m -2 ·h -1 The bonding strength is 1.22MPa (Class II board conditions), and the immersion peeling pass rate is 100% (Class II board conditions).

[0127] The formaldehyde emission results of the plywood and the corresponding log veneer of effect examples 1-4 are shown in Table 1. It can be seen that the formaldehyde emission of the prepared zero-increment plywood is basically the same as that of the log veneer, and both are ≤0.01mg / m 3 , achieving the effect of zero formaldehyde increase.

[0128] Comparison effect example 1

[0129] The same as Example 1, the only difference is that in step (2), the resin prepared in Comparative Example 1 is used as an adhesive.

[0130] The formaldehyde emission of the plywood produced in this example was measured to be 0.126 mg / m 3 The TVOC release rate is 0.54 mg·m -2 ·h -1 The bonding strength is 1.35MPa (Class I board conditions), and the immersion peeling pass rate is 100% (Class I board conditions).

[0131] Comparison effect example 2

[0132] The same as Example 1, the only difference is that in step (2), the resin prepared in Comparative Example 2 is used as an adhesive.

[0133] The formaldehyde emission of the plywood produced in this example was measured to be 0.014 mg / m 3 The TVOC release rate is 0.76 mg·m -2 ·h -1 The bonding strength is 0.34MPa (Class I board condition), and the immersion peeling pass rate is 0 (Class I board condition).

[0134] Comparison effect example 3

[0135] The same as Example 1, the only difference is that in step (2), the resin prepared in Comparative Example 3 is used as an adhesive.

[0136] The formaldehyde emission of the plywood produced in this example was measured to be 0.117 mg / m 3 The TVOC release rate is 0.38 mg·m -2 ·h -1 The bonding strength is 1.01MPa (Class I board conditions), and the immersion peeling pass rate is 100% (Class I board conditions).

[0137] Comparison effect example 4

[0138] The same as Example 1, the only difference is that in step (2), the resin prepared in Comparative Example 4 is used as an adhesive.

[0139] The formaldehyde emission of the plywood produced in this example was measured to be 0.039 mg / m 3 The TVOC release rate is 0.26 mg·m -2 ·h -1 The bonding strength is 0.87MPa (Class I board conditions), and the immersion peeling pass rate is 100% (Class I board conditions).

[0140] Comparison effect example 5

[0141] The same as Example 1, except that in step (2), the resin prepared in Comparative Example 5 is used as an adhesive.

[0142] The formaldehyde emission of the plywood produced in this example was measured to be 0.043 mg / m 3 The TVOC release rate is 0.49 mg·m -2 ·h -1 The bonding strength is 0.67MPa (Class I board condition), and the immersion peeling pass rate is 33% (Class I board condition).

[0143] Comparison effect example 6

[0144] The same as Example 1, except that the kaolin in step (2) is omitted.

[0145] Figure 4 This is a real picture of the plywood in comparative example 6.

[0146] The plywood pressed in this comparative example has cracked boards. Figure 4 The formaldehyde emission of the plywood produced in this example was measured to be 0.020 mg / m 3 The TVOC release rate is 0.12 mg·m-2 ·h -1 .

[0147] The formaldehyde emission of different types of veneers is shown in Table 1. The relevant parameters of effect examples 1-4 and comparative effect examples 1-6 are shown in Table 2.

[0148] Table 1

[0149]

[0150] Table 2

[0151]

[0152] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A modified phenolic resin for formaldehyde zero-increment plywood, characterized in that: Raw materials, calculated by mass, include: 100 parts of phenol, 118-286 parts of formaldehyde solution, 8-20 parts of urea, 25-60 parts of lignin, 25-55 parts of catalyst and 112-436 parts of water.

2. The modified phenolic resin according to claim 1, characterized in that The catalyst is sodium hydroxide and / or potassium hydroxide.

3. The modified phenolic resin according to claim 1, characterized in that The formaldehyde solution is a formaldehyde aqueous solution with a concentration of 35-55wt%; the molar ratio of formaldehyde to phenol in the formaldehyde solution is (2.0-3.0):

1.

4. A method for preparing a modified phenolic resin for formaldehyde zero-increment plywood according to any one of claims 1 to 3, characterized in that: The following steps are involved: Feeding the formaldehyde solution, urea, catalyst and water in two batches; Phenol, the first batch of water, the first batch of formaldehyde solution and the first batch of catalyst are mixed to carry out the first heating reaction; then the second batch of formaldehyde solution is added to carry out the second heating reaction; then lignin and the first batch of urea are added to carry out the third heating reaction; then the second batch of water, the second batch of catalyst and the second batch of urea are added, the temperature is lowered and the material is discharged to obtain the modified phenolic resin for the formaldehyde zero-increment plywood.

5. The preparation method according to claim 4, characterized in that: The mass ratio of the first batch of formaldehyde solution to the second batch of formaldehyde solution is (0.8-2.0):1; the mass ratio of the first batch of urea to the second batch of urea is 1:(1-1.5); the mass ratio of the first batch of catalyst to the second batch of catalyst is (1.5-2):1; the mass ratio of the first batch of water to the second batch of water is 1:(1.5-5.0).

6. The preparation method according to claim 4, characterized in that: The temperature of the first heating reaction is 60-70°C, and the time is 1-2h; the temperature of the second heating reaction is 70-90°C, and the time is 2-4h; the temperature of the third heating reaction is 70-80°C, and the time is 2-3h.

7. Use of the modified phenolic resin according to any one of claims 1 to 3 in the preparation of formaldehyde zero-increment plywood.

8. A formaldehyde zero-increment plywood, characterized in that: The modified phenolic resin described in any one of claims 1 to 3 is used as a bonding component between board layers.

9. A method for preparing the formaldehyde zero-increment plywood according to claim 8, characterized in that: The following steps are involved: (1) Peeling and drying of veneers: Peeling wood into veneers and drying them to obtain wood veneers; (2) preparing adhesive: uniformly mixing the modified phenolic resin, flour and mineral filler with a mixer to obtain a mixed adhesive; (3) Gluing and assembling: placing the mixed adhesive into a glue coating machine, using a glue coating roller to evenly coat the mixed adhesive on the surface of the wood veneer, and then assembling the veneers in the longitudinal and transverse directions to obtain plywood slabs; (4) Pre-pressing and aging: placing the plywood blank into a cold press for pre-pressing and aging to obtain a pre-pressed blank; (5) Hot pressing: sending the pre-pressed slab into a hot press for hot pressing to obtain the formaldehyde zero-increment plywood.

10. The preparation method according to claim 9, characterized in that: The mineral filler is one or more of kaolin, attapulgite and montmorillonite; the mass ratio of the modified phenolic resin, flour and mineral filler is 100:(5-30):(10-20).

Citation Information

Cited By

  • Flame-retardant wood fiber composite board and preparation method thereof

    CN120886340A